A Study of Local Vendors’ Views of Planning Global Distribution Systems: Examples from Travel Information Industry in Japan and Korea - Lee, Don D H; Wang, William Y C; Leong, Paul T M (ACIS, 2014)
Global Distribution Systems (GDS) has played a pivotal role as electronic distributors in the travel industry. Although there are two types of GDS vendors geographically –local and worldwide, almost all studies focus on worldwide GDS and do not address the differences. With theoretical lenses of Inter-organisational Systems (IOS), Systems Development Life Cycle, and home-region orientation, this research-in-progress paper is to address three research agenda: (i) a literature review on GDS in the context of IOS; (ii) a theoretical relationship between multi-nationals’ IOS and their home-region oriented IOS operations; and (iii) a proposal of research question and methods for applying to GDS planning between local and worldwide vendors. From providers’ perspective, a multiple methods approach combining a survey and case studies will be conducted with the Japan-Korea based GDS vendors. This study aims to contribute to a gap in the knowledge of Information Systems and the GDS-related travel information industry.